Rehospitalization Patterns in Pediatric Outpatients with Continuous-Flow VADs. Issue 4 (July 2017) - Hollander, Seth A.; Chen, Sharon; Murray, Jenna M.; Lin, Aileen; McBrearty, Elizabeth; Almond, Christopher S.; Rosenthal, David N.
Abstract : As continuous-flow ventricular assist devices (CF-VADs) are used increasingly in children and adolescents, more pediatric patients will be supported as outpatients. Herein we report the patterns of rehospitalization after CF-VAD implantation at a single center. We retrospectively reviewed the medical records of 19 consecutive patients who received CF-VADs between December 6, 2010 and November 5, 2016 and were discharged on device therapy. The frequency, duration, and indications for all hospitalizations between the time of implant hospitalization discharge and January 8, 2016 were analyzed. There were a total of 52 rehospitalization episodes in 16 (84%) patients over 5, 101 (median 93, interquartile range [IQR] 38, 226) follow-up days. There were a median of two (IQR 1, 3) hospitalizations per patient. The median time to first hospitalization was 14 (IQR 7, 62) days. The most common admitting diagnoses were suspected infection 13 (28%) and suspected pump thrombosis in 8 (17%). Thirty-one (60%) hospitalizations included procedures, including seven (13%) requiring device-related surgery. Overall, 89% of postimplant discharge days were spent outside of the hospital. Children with CF-VADs can be discharged with acceptable readmission rates and significant time spent out of hospital. Most patients will be rehospitalized at least once between implant hospitalization and transplantation, often within 2 weeks of hospital discharge, with the most common indications for admission being suspected infection and suspected pump thrombosis. Device-related complications necessitating surgical intervention most frequently occur in destination therapy patients who are supported for longer periods of time.